2008
DOI: 10.1002/ajh.21187
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial hypertension and left‐sided heart disease in sickle cell disease: Clinical characteristics and association with soluble adhesion molecule expression

Abstract: Pulmonary hypertension (PH), a risk factor for mortality in sickle cell disease (SCD), has pathologic features of both pulmonary arterial hypertension (PAH) and PH related to left-sided heart disease (LHD) suggesting a link between these two entities. We hypothesized that both are characterized by endothelial dysfunction and increased adhesion molecule expression. SCD patients and normal volunteers underwent a screening questionnaire, echocardiogram, and blood donation for preparation of platelet-poor plasma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 63 publications
1
33
0
4
Order By: Relevance
“…22,23 In a study of 124 adults with sickle cell disease, no relationship between erythropoietin and pulmonary hypertension was detected. 24 We, however, observed that serum erythropoietin concentration is associated with higher tricuspid regurgitation velocity in sickle cell disease patients even after adjustment for the degree of hemolysis and other significant covariates, providing evidence for the concept that erythropoietin may be related to the development of pulmonary hypertension. Circulating erythropoietin concentrations reflect the degree of tissue hypoxia, and are known to increase with lower hemoglobin concentrations and hemoglobin oxygen saturations.…”
Section: Discussionmentioning
confidence: 76%
“…22,23 In a study of 124 adults with sickle cell disease, no relationship between erythropoietin and pulmonary hypertension was detected. 24 We, however, observed that serum erythropoietin concentration is associated with higher tricuspid regurgitation velocity in sickle cell disease patients even after adjustment for the degree of hemolysis and other significant covariates, providing evidence for the concept that erythropoietin may be related to the development of pulmonary hypertension. Circulating erythropoietin concentrations reflect the degree of tissue hypoxia, and are known to increase with lower hemoglobin concentrations and hemoglobin oxygen saturations.…”
Section: Discussionmentioning
confidence: 76%
“…SCD patients may present a diagnostic conundrum because early symptoms of PH in these patients are nonspecific and may not differ from those experienced by SCD patients without PH. 25 Dyspnea is a fairly nonspecific finding in patients with SCD, observed in up to 50% of HbSS and 40% of HbSC adults, 26 and often occurs without coexistent PH. However, a history of progressive dyspnea on exertion or limitations of exercise capacity should raise concern for the presence of PH, particularly when observed in conjunction with exertional hypoxemia.…”
Section: How Should Patients Suspected To Have Ph Be Evaluated?mentioning
confidence: 99%
“…Pulmonary hypertension (PH) occurs in 10% to 30% of patients with sickle cell disease (SCD) [1][2][3] and is associated with a 17% 2-year mortality in adults. 1 Factors implicated in SCD PH include endothelial dysfunction, pulmonary vasoconstriction, and remodeling, all mechanistically associated with chronic hemolysis, hypoxia, hemostatic activation, and inflammation.…”
Section: Introductionmentioning
confidence: 99%